Monitoring of endangered fish using image processing and AI tools - Hossain, Naheen; Habib, Ahsan; Plabon, Tasharif Mehedi (Brac University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.